Catechin-Albumin Conjugates: Enhanced Antioxidant Capacity and Anticancer Effects - Tooru Ooya; Izumi Haraguchi (International Journal of Food Science)
(+)-Catechin conjugated with human serum albumin (CT–HSA) was prepared and evaluated as a drug carrier bearing anticancer effects. It was found that 2.4 mol of CT was conjugate to 1 mol HSA. The CT–HSA has an antioxidant capacity of about 3.3 times the amount of CT in the conjugate. Intracellular incorporation of the CT–HSA was analyzed by fluorescence-activated cell sorting (FACS) and confocal laser scanning microscopy (CLSM) measurements using fluorescein isothiocyanate (FITC)-labelled CT–HSA. The results indicated that the FITC-labelled CT–HSA was incorporated into HeLa cells in a concentration-dependent manner. The CT–HSA enhanced the binding of anticancer drugs (5-fluorouracil (5-Fu) and mitomycin C (MMC)) comparing with HSA, and the CT–HSA mixed with 5-Fu or MMC decreased significantly the HeLa cell viability as compared with the same concentration of each drug. In addition, intracellular reactive oxygen species (ROS) scavenging by the CT–HSA is likely to affect the anticancer effects. Thus, the CT–HSA enhanced anticancer drug efficacy in relation to controlling ROS-scavenging ability.